Determinant of consumer buying behaviour towards healthy products / Arsyad Abdul Razak - Abdul Razak, Arsyad (Faculty of Business and Management, 2011)
The main objective of this paper is to examine the determinant of consumer buying behavior represented by attitude, family influences, Price conscious, and health conscious towards healthy products.